2009
DOI: 10.1038/ncb1869
|View full text |Cite
|
Sign up to set email alerts
|

Production of offspring from a germline stem cell line derived from neonatal ovaries

Abstract: The idea that females of most mammalian species have lost the capacity for oocyte production at birth has been challenged recently by the finding that juvenile and adult mouse ovaries possess mitotically active germ cells. However, the existence of female germline stem cells (FGSCs) in postnatal mammalian ovaries still remains a controversial issue among reproductive biologists and stem cell researchers. We have now established a neonatal mouse FGSC line, with normal karyotype and high telomerase activity, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

51
820
6
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 543 publications
(886 citation statements)
references
References 30 publications
51
820
6
9
Order By: Relevance
“…More importantly, they can spontaneously generate oocytes under appropriate in vitro and in vivo conditions. This work strongly supports earlier studies [3,4], which indicated that the ovaries of female mammals maintain the ability to produce oocytes during adulthood. Altogether, these recent observations may have revolutionary implications for human health, including infertility treatments and fertility preservation npg for female patients receiving cancer treatments.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…More importantly, they can spontaneously generate oocytes under appropriate in vitro and in vivo conditions. This work strongly supports earlier studies [3,4], which indicated that the ovaries of female mammals maintain the ability to produce oocytes during adulthood. Altogether, these recent observations may have revolutionary implications for human health, including infertility treatments and fertility preservation npg for female patients receiving cancer treatments.…”
supporting
confidence: 81%
“…This assumption was greatly challenged by Johnson et al [3] in 2004, when they identified oogonial stem cells (OSCs) that sustain oocyte generation in both juvenile and adult mouse ovaries. Subsequent studies by Zou et al [4] showed that these female germline stem cells could be isolated from adult mouse ovaries by immunomagnetic bead sorting and expanded long term in vitro. However, the identification, isolation and in vitro culture conditions of human OSCs remained to be fully elucidated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They maintain their self-renewal and differentiation potentials and persist throughout the life of the mouse. Adult GSCs are thought to exist only in the testes, although the existence of GSCs in the ovary is still a subject of considerable debate (Eggan et al, 2006;Gosden, 2004;Johnson et al, 2004;Telfer et al, 2005;Zou et al, 2009).…”
Section: Developmentmentioning
confidence: 99%
“…Bir k›sm› ise atretik primordial folikül say›m›nda hata yap›ld›¤›na inanm›fl (11) veya kemoterapiden sonra nas›l 2 günde folikül yenilenmesi oldu¤una flüphe ile bakm›fl (9) veya insane overinde aktif mayoz bulgusuna rastlamam›flt›r (12) . Bu konuda tart›flmalar devam ederken yeni bir çal›flmada fare modelinde oosit ve yavru fareler difli germ hücrelerinden elde edilmifltir (13) . Çal›flmada öncelikle germ kök hücreler fareden izole edilip 6 ay kültüre edilmifl, ard›ndan bu hücreler GFP tafl›yan virus ile transfikte edilerek kemoterapi ile sterilize edilmifl fareye nakledilmifllerdir.…”
Section: Postnatal Oogenezunclassified